2011
DOI: 10.1093/bja/aeq307
|View full text |Cite
|
Sign up to set email alerts
|

Eye tracking for assessment of workload: a pilot study in an anaesthesia simulator environment

Abstract: Pupil size and heart rate reflect workload increase within simulator sessions, but they do not permit overall workload comparisons between individuals or sessions. Contrary to our assumption, the duration of fixation decreased with increased workload. Saccade amplitude did not reflect workload fluctuations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 13 publications
2
69
0
1
Order By: Relevance
“…The data were obtained in a randomised cross-over study that investigated whether eye-tracking is a feasible measure of workload fluctuation during induction of anaesthesia in a full-scale simulator environment either with or without a critical event. 12 The participants were asked to induce general anaesthesia during three different simulator sessions. To enhance familiarity with the simulator setting, the participants were told that no critical incident would occur during the first session.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were obtained in a randomised cross-over study that investigated whether eye-tracking is a feasible measure of workload fluctuation during induction of anaesthesia in a full-scale simulator environment either with or without a critical event. 12 The participants were asked to induce general anaesthesia during three different simulator sessions. To enhance familiarity with the simulator setting, the participants were told that no critical incident would occur during the first session.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8] Moreover, it was applied to measure the effects of intraoperative reading on the anaesthetist's vigilance and workload, 9 and the impact of day and night shifts on anaesthesiological workload. 10 The RPE scale is a global measure taking into account all demands 11 and its scores (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) are reported to correlate closely with actual heart rates (60-200 min À1 ). 5 In the present study, we investigated the validity and test-retest reliability of the RPE scale for the subjective assessment of workload during simulator sessions with and without critical incident.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in radiology, the NASA-TLX was used with physiological measures -gross eye and head movementsto investigate the workload imposed by two display options -mammograms on a multi viewer adjacent to workstation and a digital version for soft copy display -on clinical readers to analyse mammograms [45]. A pilot study in an anaesthesia simulator environment, motivated by patient safety, was devoted to test the hypothesis that physiological measures such as heart rate, duration of fixation and pupil size increase, whereas saccade amplitude decreases with increased severity of a simulated critical incident, being induction of general anaesthesia the primary task executed by trainee anaesthetists [44].…”
Section: Applications In Medical Domainsmentioning
confidence: 99%
“…In a study of anaesthetists' workload fluctuations during full-scale simulator sessions (Schulz et al, 2011), pupil diameter was used as one of the physiological measures of workload. It is found that pupil diameter and heart rate increased simultaneously as the severity of the simulated critical incident increased.…”
Section: Correlation To Workload In Other Tasksmentioning
confidence: 99%